A chondroprotective effect of moracin on IL-1β-induced primary rat chondrocytes and an osteoarthritis rat model through Nrf2/HO-1 and NF-κB axes. Issue 9 (24th August 2020) - Zhou, Siqi; Shi, Jiaqi; Wen, Haiyan; Xie, Wei; Han, Xiaotao; Li, Haohuan
Abstract : Moracin reduced the development of knee osteoarthritis in rats via its anti-inflammatory effect. Abstract : Osteoarthritis (OA) is a common joint disease characterized by cartilage degeneration and inflammation. Although moracin is known to play a role in anti-inflammation and anti-oxidation in several inflammatory diseases, its anti-inflammatory effect on OA remains largely unknown. Therefore, in order to explore the role of moracin in OA, we investigated the anti-inflammatory effect of moracin on interleukin (IL)-β-induced rat chondrocytes in vitro and surgically induced OA rat models in vivo . Rat chondrocytes were pretreated using moracin (0, 5, 10, 15 μmol L −1 ) and then stimulated with IL-β (10 ng ml −1 ). Results showed that moracin reduced the expression of IL-1β-induced nitric oxide (NO), prostaglandin E2 (PGE2), tumor necrosis factor-α (TNF-α), IL-6, inducible nitric oxide synthase (iNOS), and cyclooxygenase (COX)-2 in both rat chondrocytes and cell culture supernatants. Besides, IL-1β-induced degradation of aggrecan and collage II, and the high expression of matrix metalloproteinase-13 (MMP-13) and a disintegrin and metalloproteinase with thrombospondin motifs 5 (ADAMTS)-5 were also reversed by moracin. Moreover, moracin inhibited the translocation of p65 from the cytoplasm to nucleus induced by IL-1β and activated the Nrf2/HO-1 signaling pathway in chondrocytes. In OA rat models, moracin prevented cartilage of rats from destruction. All these findings above indicated that moracin could be a potentially effective drug for treating OA.